Is an efficient criminal contribution possible to prevent crimes against humanity? - Est-il possible d'utiliser efficacement les sciences criminologiques pour prévenir les crimes contre l’humanité ? - E’ possibile utilizare in modo efficiente le scienze criminologiche per prevenire i crimini contro l’umanità? - Zaffaroni E. R. (Rivista di Criminologia, Vittimologia e Sicurezza, 2009)
The article considers the role of criminal sciences dealing with the judgement and the punishment of authors of crimes against humanity. In fact, criminal sciences have to criticize preparatory acts of mass homicides, such as the preparation of their neutralization techniques, that is to say, for instance, ideologies of racial superiority, of hierarchization of human beings and of national security that legitimate torture. International criminal law may offer palliatives or possible pragmatic benefits, but the true prevention of mass murders consists in criminal judicial knowledge able to reject the values neutralization techniques, prepared by some theorists and spread over the public opinion as inducement to revenge: if criminal sciences, under the name of a pretended and impossible ideological neutrality, do not operate to fight neutralization techniques used in crimes against humanity our knowledge will be “another science that does not think”.